Understanding bracing outcomes in adolescents with idiopathic scoliosis: a mixed-methods approach - Hasan İşçi; Sena Özdemir Görgü (Frontiers in Rehabilitation Sciences)
BackgroundBrace treatment is the routinely applied conservative treatment method for Adolescent Idiopathic Scoliosis (AIS) and can yield effective results when correctly administered. Brace treatment, often initiated during adolescence, can cause individuals to face various challenges in their daily lives. This study determined the effect of spinal brace treatment on the quality of life (QoL), views, and the problems encountered regarding bracing by individuals with AIS and their parents.MethodsThis study included 44 participants aged 10–17 years using spinal braces for at least six months. Participants' QoL was assessed using the Brace Questionnaire (BrQ), a numerical evaluation scale for brace satisfaction (BS), and the extracted user and parental opinions to identify the problems affecting brace use. Individual interviews were conducted with selected groups of ten participants to examine thoroughly the factors influencing spinal brace use.ResultsPearson correlation analysis revealed positive correlation between BS and total BrQ scores and sub-parameters the regression analysis to determine the cause-and-effect relationship between BS and total BrQ scores with sub-parameters was significant (F = 7.648, p = 0.008; F = 2.935, p = 0.015, respectively). Regarding brace satisfaction and influencing factors, most participants reported breathing difficulties, dissatisfaction with the weight, color, and design of the brace, feeling chest pain, and experiencing balance problems on surveys and individual interviews.ConclusionsThis study established a correlation between BS and QoL and identified the design, weight, and material-related issues of the orthosis as significant factors influencing brace satisfaction in individuals using spinal braces.